Tutorship process in health care professions: a survey investigation in Emilia Romagna - Priami, Diletta; Sollami, Alfonso; Vivoli, Vanessa; Artioli, Giovanna (Acta Biomedica Atenei Parmensis, 2015)
The areas that we wanted to investigate include: tasks performed, tools used, formalization of the assignment, workload, empowerment and satisfaction of the function performed, and training. The results clearly show that the processes of tutoring are different for physicians and non-physician healthcare professionals. The first interesting difference is the method of assignment of mentoring. While among medical professions the function is assigned by others, tutors are often non-medical volunteers. This evidence leads to two unanswered questions: what are the criteria by which they are chosen as tutors? Do volunteers really possess the skills and ability to carry out this role? Future research should be directed towards clearly defining the profile of the “tutor” among both doctors and non-medical professionals. Another difference is the way the work of the mentor is formalized. If they are doctors, the task is assigned to them; this is not the case for non-medical professions. Despite this difference, a high percentage of both medical professionals and doctors said they did not feel valued for their role of tutor. However, differences emerge: physicians see their role as a paid tutor and / or recognized in their curriculum vitae. For non-medical professions, however, the only reward is a recognition of ECM (Educazione Continua in Medicina)credits. A common feature among professionals is that for both physicians and non-physician healthcare tutors, a system of evaluation is rarely reported. Another common feature is the skills that professionals would like to see improved. Both groups of professionals, in fact, would like to see improved teaching methods, communication strategies and reporting and evaluation systems. Finally, non-physician tutors report the same level of satisfaction, although the non-physician professionals are more satisfied in their relationship with colleagues. The degree of empowerment reveals perceived differences and similarities among the professionals. In fact, both professional groups reported the same levels of competence and impact, but differ in meaning and self-determination. More specifically, the non-medical professionals show high scores, while doctors get a higher score for self-determination. These results suggest that for increased attention to the system of evaluation and enhancement of the function tutorial we need not only to increase the satisfaction of those who act as tutors, but also to improve the tutorial process itself. Furthermore, the results suggest the carrying out of training projects for teaching and assessment methods that represent the issues that are most in demand by tutors. The training should include the use of tools for the governance process that project tutorial and apprenticeships. The responses indicate that these tools are already in use, although not as widespread and continuous.